2023
DOI: 10.1136/svn-2022-002228
|View full text |Cite
|
Sign up to set email alerts
|

Model based on single-nucleotide polymorphism to discriminate aspirin resistance patients

Abstract: BackgroundAspirin is widely used for preventing ischaemic events. About 20%–40% of patients have aspirin resistance (ASR), which prevents them from benefiting from aspirin medication. This study aimed to develop and validate a model based on single-nucleotide polymorphism (SNP) to distinguish ASR patients.MethodsWe included patients with spontaneous intracerebral haemorrhage and continuing antiplatelet therapy from a multicentre, prospective cohort study as the derivation cohort. Thromboelastography (inhibitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…11 In addition, laboratory tests have found that in some patients aspirin does not inhibit thromboxane A2 production, which is called biochemical aspirin resistance. 12 At present, studies have shown that there are many reasons leading to aspirin resistance, such as poor drug compliance and insufficient drug dose, non-cyclooxygenase 1 mediated platelet activation, obesity and gene polymorphisms; [13][14][15][16] of which gene polymorphisms are the focus of considerable research in aspirin resistance at present. [17][18][19][20] Platelets contain a large number of highly polymorphic transmembrane glycoprotein receptors encoded by two or more isomeric alleles.…”
Section: Aspirin Resistance and Gene Polymorphismsmentioning
confidence: 99%
“…11 In addition, laboratory tests have found that in some patients aspirin does not inhibit thromboxane A2 production, which is called biochemical aspirin resistance. 12 At present, studies have shown that there are many reasons leading to aspirin resistance, such as poor drug compliance and insufficient drug dose, non-cyclooxygenase 1 mediated platelet activation, obesity and gene polymorphisms; [13][14][15][16] of which gene polymorphisms are the focus of considerable research in aspirin resistance at present. [17][18][19][20] Platelets contain a large number of highly polymorphic transmembrane glycoprotein receptors encoded by two or more isomeric alleles.…”
Section: Aspirin Resistance and Gene Polymorphismsmentioning
confidence: 99%